Kant's Political Theory : Interpretations and Applications - Ellis, Elisabeth (Book collections on Project MUSE., 2012)
"A collection of essays examining Immanuel Kant's lectures and minor writings as well as his political essays. Offers a comprehensive introduction to Kant's political thought from a position of engagement with modern political and philosophical questions"--Provided by publisher.